Implementation of PBL Model to Improve Learning Outcomes Class X IPA 1 SMAN 2 Labuapi - Dari, Sri Wulan; Handayani, Baiq Sri; Hadratullaili, Hadratullaili (Biota, 2023)
Improving learning outcomes can be achieved by implementing models that cater to students' learning needs and are integrated with contextual issues as part of the learning process. Problem Based Learning (PBL) is an effective model widely used to facilitate student-centered learning activities and promote problem-based learning. The implementation of PBL directs learning towards contextual issues and the relevant experiences of students, resulting in improved learning outcomes. This study aims to enhance student learning outcomes of class X IPA 1 through the implementation of the PBL model. It employs Classroom Action Research conducted in two cycles with stages including planning, implementation, observation, and reflection. Data was gathered through observation, pre-tests, and post-tests in both cycles. Data analysis techniques involved both qualitative and quantitative analyses. The results revealed an initial class average score of 70.00 in the first cycle, achieved through the implementation of the PBL model. The average class score further improved to 85.00 in the second cycle, obtained through reflective practices using the PBL model and discussion methods. This demonstrates that employing the PBL model alongside discussions enhances the learning outcomes of class X IPA 1 students in the topic of ecosystems.